2019
DOI: 10.1002/aic.16882
|View full text |Cite
|
Sign up to set email alerts
|

Hopper flows of mixtures of spherical and rod‐like particles via the multisphere method

Abstract: The discharge of granular media from hoppers plays a vital role in many solids handling operations. The dynamic flow of poly-disperse non-spherical particles differs markedly from mono-disperse spheres and highlights the need to rigorously account for particle shape effects. The multi-sphere discrete element method (MS-DEM) was utilized here to examine the bulk packing fraction, discharge rate, collisional stress tensor, and order parameter of a bidisperse sphere-rod mixture evacuating a hopper. A modified for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The velocity distribution curve gradually flattens along the upward direction and eventually forms a plateau in the horizontal central zone, that is, a plug flow zone is formed in the upper part of the flowing zone. Such phenomenon has also been experimentally observed for funnel flow discharge 21–25 . Szabo et al 25 found the formation of plug flow zone was closely related to the particle shape.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The velocity distribution curve gradually flattens along the upward direction and eventually forms a plateau in the horizontal central zone, that is, a plug flow zone is formed in the upper part of the flowing zone. Such phenomenon has also been experimentally observed for funnel flow discharge 21–25 . Szabo et al 25 found the formation of plug flow zone was closely related to the particle shape.…”
Section: Resultssupporting
confidence: 52%
“…For funnel flow discharge, the flowing zone width first increases with vertical position and then keeps nearly constant 18–20 . Experimentally, it has been found that granular materials in the upper part of the flowing zone could be in plug flow state and notable velocity gradient only appears in the narrow shear region in between the flowing and stagnant zones 16,21–25 . Thus, if we consider the interface between flowing and stagnant zones as a rough surface, the flowing pattern of funnel flow is actually the same as that of mass/semi‐mass flow.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of numerical simulations of silo discharge of nonspherical particles with multisphere-DEM include rods 29 and mixtures of spherical and rodlike grains. 30 Many features of silo discharge are not only qualitatively but even quantitatively similar in two-dimensional (2D) and threedimensional geometries. The 2D container geometry offers the advantage that internal structures and dynamic processes can be directly observed with non-invasive optical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Lattanzi and Stickel 26 found that the discharge rates of rod-like particles from hopper can increase about 20% when the number of component spheres is increased from 5 to 11. These researches revealed the influence of shape resolutions on the accuracy of glued sphere simulations.…”
Section: Introductionmentioning
confidence: 99%
“…You and Zhao 25 found the computation speed was reduced by a factor of two when the number of glued spheres was increase from 16 to 32 in the simulation of ellipsoidal particles packing. Lattanzi and Stickel 26 found that the discharge rates of rod‐like particles from hopper can increase about 20% when the number of component spheres is increased from 5 to 11. These researches revealed the influence of shape resolutions on the accuracy of glued sphere simulations.…”
Section: Introductionmentioning
confidence: 99%